The trouble with 'trust' in news media. Issue 4 (1st October 2016) - Fisher, Caroline
ABSTRACT: Questions surrounding trust in news media have preoccupied scholars for almost a century. Based on a review of interdisciplinary literature, this paper provides an overview of the evolution of conceptions of news trust over the past 80 years. In doing so, this paper highlights key problems with the question of trust in this context. First, despite the volume of research on this topic, there is no agreed definition or measure of 'trust' in news media. Second, there is a growing disconnect between the normative ideal of an informed citizenry and the complex range of influences on perceptions of news credibility in the digital era. Third, in an age of uncertainty about the veracity of online information, is 'trust' in news even desirable? In response to these issues, this paper asks whether research based on undefined general questions about public 'trust' in news media continues to be relevant.